Pemberdayaan UMKM melalui Digitalisasi dan Inovasi Branding di Pondok Ranji, Ciputat Timur - Mohammad Naufaldi; Yassin Syuhada Akbar; Thurisina Rahmawati; Ricky Budi Utomo; Muhammad Dwi Rizqi; Ernawati; Dhiya Aafreen Kaysan Jalil; Lutfillah Afiy Hidayanti; Faaris Hassan Kamal; Nurhuda; Yanti Budiasih (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service program aims to empower small-scale micro businesses through digital transformation and branding enhancement. The program targets micro-entrepreneurs in Pondok Ranji, Ciputat Timur, who have limited knowledge of digital marketing and financial management. The method involves workshops, mentoring, and door-to-door assistance to introduce tools such as QRIS, Google Maps, and social media marketing. The results show that partners successfully adopted basic digital tools, created online business profiles, and improved their visual branding. The project fosters greater business visibility, stronger customer engagement, and enhanced financial literacy among participants.